Asking a Better Question: Development and Evaluation of the Need For Trauma Intervention (NFTI) Metric as a Novel Indicator of Major Trauma. Issue 3 (May 2017) - Roden-Foreman, Jacob W.; Rapier, Nakia R.; Yelverton, Luanna; Foreman, Michael L.
Abstract : Many existing metrics, such as Injury Severity Score (ISS), cannot fully describe many trauma patients because of comorbidities. This study developed and evaluated the Need For Trauma Intervention (NFTI) metric as a novel indicator of major trauma. The NFTI metric was developed from an analysis of 2, 396 trauma patients at a Level I trauma center. Six commonly recorded registry variables were found to be indicative of major trauma and comprised the NFTI criteria: receiving packed red blood cells within 4 hr; discharge from the emergency department (ED) to the operating room within 90 min; discharge from the ED to interventional radiology; discharge from the ED to the intensive care unit (ICU) with an ICU length of stay (LOS) of 3 or more days; mechanical ventilation outside of procedural anesthesia within 3 days; or death within 60 hr. Patients meeting any NFTI criteria are classified as having major traumas and, therefore, needing trauma activations (NFTI+). Need For Trauma Intervention was tested in an overlapping sample of 9, 737 patients. Being NFTI+ was associated with higher trauma activation levels, older age, higher ISS, worse ED vitals, longer hospital LOS, and mortality. Only 13 of 561 deaths were not NFTI+ and all were in patients with do not resuscitate (DNR) orders; using ISS greater than 15 missed 73 mortalities, 46 with DNR orders. Results suggest that NFTI provides a comprehensive view of both anatomy and physiology in a manner that self-adjusts for age, frailty, and comorbidities as long as care teams adjust their treatments. Need For Trauma Intervention appears to be a unique, simple, and effective tool to retrospectively identify major trauma, regardless of ISS. Abstract : Supplemental Digital Content is Available in the Text.